Antibiotic Resistance Traits and Molecular Subtyping of Staphylococcus aureus Isolated from Raw Sheep Milk Cheese. Issue 10 (3rd September 2014) - Spanu, Vincenzo; Scarano, Christian; Cossu, Francesca; Pala, Carlo; Spanu, Carlo; De Santis, Enrico P. L.
Abstract The main objective of the present research was to evaluate the antibiotic resistance profiles of Staphylococcus aureus isolated from raw sheep milk cheese. A total of 150 strains were isolated from curd cheese samples and identified as S. aureus. The survey on antibiotic resistance was carried out on 47 strains, selected among isolates showing differences in the banding pattern after Pulsed Field Gel Electrophoresis (PFGE) screening or, belonging at the same pulsotype but isolated from different cheese samples. On selected strains antimicrobial resistance against ampicillin, penicillin, cloxacillin, tetracycline, erythromycin, and vancomycin was assessed by broth microdilution method. The presence of the genes coding for antibiotic resistance and virulence factors (agr alleles, sea‐see, and tst) was also investigated by PCR. Thirty‐one isolates belonging to agrI and agrIII groups carried at least one gene coding for enterotoxins or toxic shock syndrome toxin. Approximately 60% of the selected strains were susceptible to the tested antibiotics. Twelve of 47 isolates showed multiple resistance against ampicillin and penicillin. Only 1 strain, represented by a unique PFGE profile showed simultaneous resistance to ampicillin, penicillin and cloxacillin. Single resistance against tetracycline was found in 5 isolates belonging to 2 different pulsotypes. The results of this study suggest that the recovery of S. aureus resistant strains in raw milk cheese samples is quite common but it is limited to few antibiotic classes, mainly β‐lactams and tetracyclines. None of the strains showed resistance to erythromycin and vancomycin.